CPD preferences and activities of general practitioners, registered pharmacy staff and general practice nurses in NHS Scotland – a questionnaire survey. Issue 4 (4th July 2019) - Cunningham, David E.; Alexander, Anna; Luty, Sarah; Zlotos, Leon
ABSTRACT: In the United Kingdom, taking part in continuing professional development (CPD) is required for revalidation for general practitioners, general practice nurses and registered pharmacy staff – pharmacists and pharmacy technicians. The literature has many research studies which describe one profession's activities, or a specific learning method or topic. Few studies compared the CPD preferences across these four professional groups or compared their CPD activity. A survey was designed by the authors with assistance from colleagues within NHS Education for Scotland (NES). It was sent to the four professions and 2, 813 clinicians responded. More than 75% of all respondents spent between 0 and 10 h per month on CPD activities. Participation in formal Protected Learning Time (PLT) varied across different NHS boards in NHS Scotland and ranged from 23.9% of respondents in the board with the lowest participation, to 68.6% in the board with the highest participation. All professions indicated a greatest preference to learn with other members of their profession. The preferred time for learning during the day varied amongst professions. The CPD activity of greatest preference for all professions was discussion with peers. There were some minor differences in learning preferences and activities from professionals working in remote and rural areas and in areas of socio-economic deprivation in Scotland.